Konsep Nilai dalam Peradaban Barat - Dinar Dewi Kania (TSAQAFAH, 2013)
The Western’s conception of  values, morals and ethics are so different with Islamic conception. In fact, there is difference about it between western scholars. These is a consequence from secularization that spread upon the whole Europe  after  their  people’s  believe  of  church’s  conductiveness  disappeared. This secularization impacts to the separation between religion’s doctrines and life activities as politic, education even to the marriage. In the end, Western society  considers  the  values  of  religion  are  just  subjective  phenomenal  that experienced by individual and are not universally. Religion has space its self that different  with  space  of  non-religion. The  value  and  moral  concept in West would  be  evolved  and  developed  according  to  western  society’s  conception of  human  being  reality,  religion,  sciences  and  life  it’s self. This paper  has  a purpose to describes western scholar’s thoughts about values and moralities chronologically, starting from medieval centuries when Churches have the power of high legitimacy in western society until renaissance era and then describing about glorious era that the western scholar’s thoughts still influences the concept of values in this century.